Dramatic inversion of charge polarity in diketopyrrolopyrrole-based organic field-effect transistors via a simple nitrile group substitution - Yun, Hui-Jun (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.